Effectiveness of peer group-based psychosocial empowerment training on high-risk behaviors in male secondary school Students at risk for behavioral issues - Rahmatzadeh, Abolghasem; Monirpour, Nader; Zargham Hajebi, Majid (Social Determinants of Health, 2026)
Background: Adolescence is a critical developmental stage where high-risk behaviors can jeopardize well-being and future outcomes. This study evaluated the efficacy of peer group-based psychosocial empowerment training in reducing high-risk behaviors among male secondary school students at risk for behavioral issues in Tehran, Iran. Methods: This quasi-experimental study employed a two-group, pre-test, post-test, and three-month follow-up design with a control group. A purposeful sample of 40 at-risk male students, identified through teacher reports and a high-risk behaviors questionnaire, was randomly assigned to a peer-led experimental group (n=20) or a wait-listed control group (n=20). The experimental group received eight 90-minute sessions of psychosocial empowerment training facilitated by trained peers. Data were collected using a validated high-risk behaviors questionnaire (42 items, seven subscales). Repeated measures ANOVA and Bonferroni post-hoc tests were used to analyze group differences over time, with effect sizes (η²) reported. Results: The peer-led intervention significantly reduced high-risk behaviors, including cigarette/hookah use, alcohol/substance consumption, aggressive behaviors, suicidal ideation/attempts, running away, and opposite-sex relationships (F=59.22, P<0.001, η²=0.61, 95% CI [14.63, 22.83] for total score). These reductions were sustained at the three-month follow-up, indicating a robust effect of the intervention on vulnerable adolescents. Conclusion: This study demonstrates the efficacy of peer group-based psychosocial empowerment training as an effective strategy for reducing high-risk behaviors among at-risk male adolescents. The findings support the integration of peer-led interventions into school-based mental health programs to enhance resilience and promote positive youth development.